Personal Hygiene Garbage Transport Officers In The Dampit Sub-District TPS Malang - Wardhani, Isya Septya; Byba Melda Suhita; Setyo Budi Susanto (Universitas STRADA Indonesia, 2018)
Personal hygiene is a way of caring for humans to maintain their health. Maintenance of individual hygiene is needed for individual comfort, safety and health. The garbage transport workers are people who are always in a dirty environment and vulnerable to health problems. The purpose of the study was to find out the description of personal hygiene of garbage transport officers in the Dampit Sub-District TPS Malang. The qualitative research design with the phenomenology approach and the informants were 5 waste informants in the Dampit Sub-district TPS. The sample of this study is the garbage transport officer who does not use personal protective equipment in full. The sampling technique used was purposive sampling. The research instrument is the researcher himself. Data collection methods are in-depth interviews and observations and the tools used are mobile phones and documentation. In this study, the existing data will be tested for validity with the Trianggulation technique using Triangulation of Sources, namely the Head of the UPT Garbage Service and Supervisor of the Dampit District TPS. The results showed that the garbage transport officers had carried out personal hygiene activities in their daily lives, but in reality their knowledge, attitudes and beliefs were good enough and some were still lacking and had not formed good behavior in maintaining personal hygiene. In this study the problems encountered were the knowledge of officers about correct personal hygiene. The attitude of the officers is still influenced by the lack of maximum social support from related agencies. The belief that officers are lacking in maintaining personal hygiene because they have never been exposed to an illness is influenced by a lack of knowledge and understanding of the importance of maintaining personal hygiene.